Patterns of residential burglary and urban environments, 1982-1983 - Herbert, David T. (UK Data Service, 1983)
The aims of this survey were: to identify patterns of burglary and related forms of residential crime; to identify vulnerable areas and examine bases of vulnerability; to research attitudes within different types of residential area and policy implications.